2015
DOI: 10.5430/ijhe.v5n1p111
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Students’ Reading Anxiety with Regards to Some Variables

Abstract: The aim of this study is to determine students' views on reading anxiety with regards to variables of gender and grade levels of the students and socio-economic level of the schools. To this end, Melanlioglu's (2014) "Reading Anxiety Scale", a 5 point likert scale consisting of 14 questions, was used. The scale consists of following sub-dimensions: planning of reading process, factors supporting reading, reading comprehension and analysis. The universe for the study consists of middle school students in a city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…As anxiety is linked to speaking skills, recent research has found that ESL learners face anxiety related to reading, leading to poor reading performance and contributing contrast result to speaking (Song, 2018). The anxiety contributor with relation to reading skill has drawn researchers' attention to unravel the effect of reading anxiety on EFL learners (Sari & Sumatra, 2017;Aisyah, 2017;Muhlis, 2017;Zarei & Ghoushchi, 2018) and also on ESL learners (Kiya, 2015;Kilinc & Yenen, 2015;Mei & Michelle, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…As anxiety is linked to speaking skills, recent research has found that ESL learners face anxiety related to reading, leading to poor reading performance and contributing contrast result to speaking (Song, 2018). The anxiety contributor with relation to reading skill has drawn researchers' attention to unravel the effect of reading anxiety on EFL learners (Sari & Sumatra, 2017;Aisyah, 2017;Muhlis, 2017;Zarei & Ghoushchi, 2018) and also on ESL learners (Kiya, 2015;Kilinc & Yenen, 2015;Mei & Michelle, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another research done by Kiya (2015) on Iranian University students reflected a positive relationship between EFL classroom and reading anxiety. Kilinc and Yenen (2015) investigated the level of reading anxiety based on Melanlioglu's (2014) 5 Likert reading anxiety scale consist of four sub-dimensions which are planning of reading process, factors supporting reading, reading comprehension and analysis found that the respondents "sometimes" face anxiety in reading comprehension and analysis and found to "rarely" have any anxiety in the area of planning of reading and factors supporting reading. However, research was done by Mei and Michelle (2014) exploring the relationship between reading anxiety and reading performance among Chinese learners learning English as a second language, it was found that there is a negative relation between L1 and L2 reading performance and reading anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study of Zhou (2017) investigated reading anxiety among learners of Chinese students in the US, and the findings showed that the major sources of reading anxiety are comprehension worries, unknown pronunciation, unfamiliar topics, and uncomfortability to read aloud. Kilinc and Yenen (2016) among middle school in Turkey showed that that students' reading anxiety increased as they moved from one class to another. Recently, Al-Sohbani (2018) investigated reading anxiety among Yemeni secondary school students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results speci ed both Foreign Language Reading Anxiety Scale (FLRAS) and Foreign Language Reading Strategy Use Scale (FLRSUS) had important subcomponents also, more than half of the students commonly did not feel anxious when reading English, and were con dent in and pleased with their English reading pro ciency. Also, Kilinc and Yenen (2016) regulate students' outlooks on reading anxiety with regards to variables of gender and grade levels of the students and socioeconomic level of the schools. The results of the study point out that students sometimes had anxiety in reading comprehension and analysis sub-dimensions, whereas they hardly ever had anxiety in the sub-dimensions of planning reading process and factors supporting reading.…”
Section: Foreign Language Reading Anxiety (Flra)mentioning
confidence: 99%